Distribution and Abundance of Brant (Branta Bernicla) on the Central Arctic Coastal Plain of Alaska - Stickney, A.A.; Ritchie, R.J. (ARCTIC, 1996)
The distribution and abundance of brant (Branta bernicla) were surveyed on the central Arctic Coastal Plain of Alaska between 1989 and 1992. Numbers of nests ranged between 319 and 517 in 43 to 67 locations. More than 70% of the nesting locations consisted of >=5 nests; only one or two locations had >=100 nests in any year. Brant attempted to nest every year at primary sites, but less frequently at secondary and solitary nest sites. Estimated numbers of nesting brant averaged 800 birds (range=630-1064); failed and nonbreeding brant ranged between 293 and 740 birds. During brood-rearing, approximately 900 to 3200 brant (26% to 48% goslings) used coastal habitats within the study area. Some coastal habitats were used annually; others were used only intermittently. Inland lakes were used by only a few brant each year. The earliest comparable data from the mid-1970s suggest that the population of brant in the study area has remained fairly stable. Factors affecting distribution of brant within the study area included environmental conditions, such as snowmelt and persistent ice, and predators. Indirect effects of oil development on brant distribution may include temporarily altered hydrologic regimes and elevated predator populations. Entre 1989 et 1992, on a établi un relevé de la distribution et de l'abondance de la bernache cravant (Branta bernicla) dans la partie centrale de la plaine côtière de l'Arctique en Alaska. Le nombre de nids allait de 319 à 517 dans 43 à 67 sites. Plus de 70 p. cent des sites de nidification comportaient <= 5 nids; seuls un ou deux sites abritaient >= 100 nids au cours d'une année. La bernache essayait chaque année d'établir son nid sur un site primaire, mais moins fréquemment sur un site secondaire ou solitaire. Le nombre estimé de bernaches qui nichaient était d'en moyenne 800 oiseaux (gamme: de 630 à 1064); le nombre de bernaches dont les oeufs n'éclosaient pas et de celles qui ne se reproduisaient pas allait de 293 à 740. Au cours de l'élevage de la couvée, environ ...